Immunological Abnormalities in Insulin Receptors on Cultured EBV-Transformed Lymphocytes From Insulin-Resistant Patient With Leprechaunism - Cama, Alessandro; Marcus-Samuels, Bernice; Taylor, Simeon I (Diabetes (New York, N.Y.), 1988)
Defects in insulin-receptor structure can impair insulin-receptor function. We have previously identified qualitative abnormalities in insulin binding to insulin receptors from an insulin-resistant patient (Lep/Ark-1). The defects in insulin binding are probably caused by a defect in receptor structure. In this study, we used immunological probes to investigate the structural defect(s) responsible for the abnormal function. Several anti-receptor antibodies were impaired in their abilities to bind to the insulin receptor of Lep/Ark-1. For example, monoclonal antibody MoAb-51 was much less effective in inhibiting binding to insulin receptors from Lep/Ark-1 (ID50 70 nM) than to those of normal subjects (ID50 8 nM). In addition, there was a 10-fold reduction of the avidity with which human polyclonal antibody B-d immunoprecipitated the patient's insulin receptors. The avidity of antibody B-10 was also reduced, although to a lesser extent. In contrast, several site-specific antibodies against epitopes on the β-subunit of the receptor bound to receptors from Lep/Ark-1 with normal avidity. The data with monoclonal and polyclonal antibodies are consistent with the hypothesis that the structural defect resides in the extracellular domain of this patient's insulin receptor. The normal immunoreactivity of two putative phosphorylation sites on the β-subunit with site-specific antibodies gives further support to the conclusion that this patient's receptors have normal tyrosine kinase activity.